International investment law and comparative public law - Schill, Stephan (Stephan W.) (Oxford : Oxford University Press, 2010)
International investment law is one of fastest-growing areas of law, but it is plagued by the vagueness of many investors' rights & unpredictable investment tribunal decisions. This book analyses international investment law through the lens of comparative public law to clarify investment treaty obligations & arbitral procedure.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Investments, Foreign (International law); Investments -- Law and legislation; Comparative law